Cinderella pneumatology as an intercultural discussion: personal, church, and theological experience sequence - Christar Arstilo Rumbay (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
Pneumatology shares rich discussion to theology and its brances knowledge. Indeed, intercultural discussion to the account receives attention but has no solid ground, where I borrow Moltmann??